2017
DOI: 10.17977/um015v45i12017p050
|View full text |Cite
|
Sign up to set email alerts
|

Formative Assessment in Efl Classroom Practices

Abstract: This study investigated the challenges and opportunities of formative assessment in EFL classes. It made use of qualitative research design by using indepth interviews to collect the required data. Three teachers and three students were involved as research participants in this study and they were intensively interviewed to get valid and reliable data regarding their understanding of formative assessment and the follow up actions they took after implementing formative assessment. The results of this study show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 9 publications
3
43
1
Order By: Relevance
“…Past studies varied with different aims, methods, results, and they "indicated the importance of FA to improve the quality of the teaching and learning process in the classroom" Widiastuti & Saukah (2017). Some studies focused on the reasons for not conducting FA in EFL classrooms as in Tan (2004); Dunphy (2010); Bennet (2011); Heitink et al (2015).…”
Section: Previous Studiesmentioning
confidence: 99%
“…Past studies varied with different aims, methods, results, and they "indicated the importance of FA to improve the quality of the teaching and learning process in the classroom" Widiastuti & Saukah (2017). Some studies focused on the reasons for not conducting FA in EFL classrooms as in Tan (2004); Dunphy (2010); Bennet (2011); Heitink et al (2015).…”
Section: Previous Studiesmentioning
confidence: 99%
“…It has been challenging to determine whether the use of formative assessments really improve learning or if they are simply used as grading tools. Therefore, Widiastuti and Saukah (2017) have conducted qualitative research to analyze teachers' understanding of formative assessments and how they influenced the follow-up actions in response to students' learning problems. The researchers included three junior high school teachers and three junior high school students in their study.…”
Section: Unveiling Teacher Understanding Of Formative Assessmentsmentioning
confidence: 99%
“…Furthermore, the research findings and analysis of Foster and Poppers (2009), Kuzel and Shumba (2011), as well as, Widiastuti and Saukah (2017) explain that when teachers do not have a clear understanding of formative assessment practices, it is difficult for them to design and provide useful follow-up activities to enhance EFL students' learning. Therefore, as Saito's and Inoi's (2017) highlights it is relevant to know about formative assessments' methods and purposes, as well as, how to provide feedback to the learners before implementing them in class.…”
Section: Conclusion Encouraging and Challenging Findingsmentioning
confidence: 99%
“…Ayuanita (2013) explains that formal assessment is designed in deliberately using the conventional feedback, conducted in a certain time frame, prepared for (and some feared) by the students, and characterized by offering specific scoring or grading formats. The use of formal assessment is merely used to make a judgment for the students' ability and to generate the students' improvement to reach the highest standard (Widiastuti & Saukah, 2017). In the current condition, the use of formal assessment needs to be improved, therefore the teacher must develop the assessment in a more stylish design.…”
Section: Introductionmentioning
confidence: 99%